Modelling of Safety Characteristics of Redundant Safety – Related Transmission System via Markov’s Analysis - Jan Rofar; Maria Franekova; Peter Holecko (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with problems of safety features modelling using a safety-related redundant transmission system as part of a safety –critical control system. The main part of the paper is oriented to the Markov model description which was realised for a 1oo2 redundant transmission system. The results of quantitative safety analyses are valid for the fail safe redundant transmission system – Profibus DP with a ProfiSafe safety profile.